Over het aansluiten van puntenvelden (2): De aansluitingsvereffening. - Teunissen, Peter; Salzmann, M.A.; de Heus, H.M. (1987)
On the adjustment for the connection of pointfields: In this article a general method is derived for connecting overlapping pointfields. In particular attention is given to randeficiencies in the coordinate covariance matrices. A regularization method for singular covariance matrices is given. It is shown that the linear least-squares estimators of the coordinates and transformation parameters are invariant for the regularization method. No explicit use is made of the theory of generalized inverses. Some numerical examples are given.